Personal technique for wrist dorsal approach - Marcuzzi, A.; Leigheb, M.; Russomando, A.; Landi, A. (Acta Biomedica Atenei Parmensis, 2014)
In hand disorders surgical procedures are more and more widely used and often it’s necessary to approach the wrist by the dorsal way. Beneath anatomy of this region is well known, there is still room enough to develop new surgical exposure techniques mostly related to physiology and biomechanics. Our goals are to present an innovative surgical dorsal exposure of the wrist, to show its use for different problems solving, and to evaluate its mini-invasive and functional outcome. Our inedited surgical technique is presented. Since November 1999 to February 2008, this technique has been used by the same surgeon in 60 cases for different pathologies and procedures: 14 SNAC-SLAC wrists III-IV treated by proximal row resection and ResurfaceCapitate Pyrocarbon Implant (RCPI), 2 Fenton syndromes by bone graft and RCPI, 6 SNACSLAC II by proximal row resection +/- radial styloidectomy, 2 SLAC III by scaphoidectomy and capito-lunate arthrodesis, 12 scapho-lunate recent dissociations by ligamentoplasty (double approach), 4 scapho-lunate inveterate dissociations by Cuenod Saffar-Romano modified technique and 4 by synthetic ligaments, 1 fracture of the scaphoid proximal pole by synthesis-revascularization-S.L.ligament reconstruction, 15 Kienbock’s diseases revascularized by II m.c. artery +/- radial osteotomy. Patients have been evaluated at follow up through the DASHdisability questionnaire, theMayo score for the force, ROM, pain, satisfaction grade. Results are good and encouraging for these applications. In conclusion this new technique with its limited exposure permits an early mobilization with a lower risk of stiffness and can be considered mini-invasive.